2006
DOI: 10.1080/14783360600588216
|View full text |Cite
|
Sign up to set email alerts
|

An empirical research on the institutional theory of downsizing: Evidence from MNC's subsidiary companies in Taiwan

Abstract: The research uses 18 business cases to verify the institutional theory of downsizing (McKinley et al., 2000). It shows that the rationale behind enterprises' downsizing practices is mixed with economic factors, institutional factors and social cognition processes. Moreover, the influences of institutionalization appear not only on the motivation of downsizing, but also on the practices used by enterprises to execute the downsizing strategies. The implications are: institutionalization would influence the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…This article offers two meaningful results: first, the rationale for downsizing seems to be due to economically rationale motives more than legitimacy-driven purposes. Namely, this result does not reinforce the validity of institutional theory of downsizing advocated by McKinley et al (1995), McKinley et al (2000), and Tsai et al (2006). As expected by past downsizing research (Chadwick et al 2004;Guthrie and Datta 2008), the results obtained in this study support the prevailing assumption that downsizing exerts an adverse effect on perceived market performance, namely sales growth.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This article offers two meaningful results: first, the rationale for downsizing seems to be due to economically rationale motives more than legitimacy-driven purposes. Namely, this result does not reinforce the validity of institutional theory of downsizing advocated by McKinley et al (1995), McKinley et al (2000), and Tsai et al (2006). As expected by past downsizing research (Chadwick et al 2004;Guthrie and Datta 2008), the results obtained in this study support the prevailing assumption that downsizing exerts an adverse effect on perceived market performance, namely sales growth.…”
Section: Discussionsupporting
confidence: 59%
“…McKinley et al (1995) argues that constraining, cloning, and learning act as three major institutional causes of implementing a massive employee reduction. Institutional theory of downsizing assumes that firms reduce uncertainty and gain legitimacy by imitating downsizing practices by those firms seen as being accepted by the members of a society (Tsai, Wu, Wang and Huang 2006). Tsai et al's (2006) empirical study of the downsizing decision by 18 foreign MNCs in Taiwan found that downsizing was attributable to commands from hierarchy, a widely shared social norm, and learning from benchmark corporations.…”
Section: Causes Of Downsizingmentioning
confidence: 99%
See 2 more Smart Citations
“…economic downturns, declining demand). Downsizing, as seen through an institutional theory lens, often occurs because it is deemed to be a legitimate strategy and therefore worthy of mimicking (Tsai et al, 2006).…”
Section: Downsizingmentioning
confidence: 99%